Effects of hemoperfusion associated with hemodialysis on the mineral metabolism of maintenance hemodialysis patients - YANG Fu-yan; SONG Juan; DUAN Kun (Linchuang shenzangbing zazhi)
Objective To investigate the effects of hemoperfusion（HP）associated with hemodialysis（HD）on the mineral metabolism of maintenance hemodialysis（MHD）patients with uremia.Methods 110 MHD patients in the Hemopurification Center of Xinxiang from January2012 to August2013 were enrolled in this study.According to random number table method,110 cases of MHD were divided into two groups.Fifty-five patients with uremia in hemodialysis（HD）group received 3 times of routine HD treatments per week,and 55 patients with uremia in HP+HD group received one time of HP plus HD（HP+HD）and 2 times of routine HD treatment.The routine treatment time was 4h.The evaluation indexes of all patients were collected one day before HD and 3 months after treatment,including serum calcium,serum phosphorus,intact parathyroid hormone（iPTH）and alkaline phosphatase（ALP）.Results There were no statistically significant differences in the levels of serum calcium,phosphorus,iPTH and ALP between two groups before treatment（P>0.05 for all）.After treatment for 3 months,the level of serum phosphorus was significantly lower than that before treatment in the HD group.In the HP+HD group,the levels of serum phosphorus,iPTH and ALP were significantly decreased after treatment（P<0.01）,and the level of serum calcium was higher than that before treatment.The level of serum calcium was higher in HD group than that in HD+HP group（P<0.05）,and the level of serum ALP was obviously decreased in HD+HP group（P<0.05）after treatment.The levels of serum phosphorus and iPTH in HP+HD group were decreased significantly after treatment（all P<0.01）.Conclusions As compared with ordinary HD,HP+HD can effectively remove serum phosphorus and decrease the iPTH and ALP,thus improving the abnormal mineral metabolism of MHD patients with uremia.